Pengaruh Quality of Work Life (QWL) dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. Tunas Dwipa Matra Lampung - Muhammad Ichsan Hadjri; Kintan Dwi Amelia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was conducted to determine the effect of quality of work life and job satisfaction on employee performance (empirical study at PT. Tunas Dwipa Matra Lampung). The population in this study were all employees of PT. Tunas Dwipa Matra Lampung totaling 442 employees. The sampling technique in this study used the simple random sampling method, namely randomizing from a total population of 442 employees with the Slovin formula where the error limit is 5% or 211 employees as sample test respondents. The results of multiple linear regression analysis show that quality of work life and job satisfaction have a positive and significant effect on employee performance. In terms of quality of work life, companies need to consider employee welfare, such as holding recreation. This can help reduce stress and anxiety, which can have a positive impact on mental health. And in business activities, companies need to provide opportunities for all employees according to their respective duties and responsibilities, thus creating work that motivates workers, achieves high job satisfaction, and produces increasingly qualified employees.